THE FOREST VEGETATION OF THE CHERNIHIV POLESIE LOESS “ISLANDS” - Yakovenko, Oleksandr (Biota. Human. Technology, 2024)
The purpose of the study. To find out the distribution, syntaxonomic composition and peculiarities of the Chernihiv Polesie loess ”islands” forest vegetation. Methodology. The materials were collected during field research in 2008–2021. The field study of vegetation was carried out using geobotanical methods (169 relevé s). Relevés were carried out on areas of 400–625 m2. The projective coverage of plant communities layers and coverage of all the species was noted. The plant communities were identified and named according to publications on the ecological and floristic classification of vegetation. Scientific novelty. The syntaxonomic composition of the Chernihiv Polesie loess ”islands” forest vegetation was established. The plant communities distribution was clarified. The comparison of the forest vegetation classes representation of the loess “islands” in the Chernihiv Polesie was made. Conclusions. The communities of the Chernihiv Polesie loess ”islands” forest vegetation is represented by 15 associations belonging to 9 unions of the 6 orders of the 6 classes. The ruderal forest nitrophilous communities of the Robinietea Jurko ex Hadač et Sofron 1980 class formed in the places of anti-erosion forest plantings in ravines and gullies. The significant development of the ravines and beam network within the Berezna-Mena-Sosnytsia loess “island” is the reason for the high frequency of of this class associations in it territory. The wetland communities of shrubs (Salicetea purpureae Moor 1958) and trees (Alnetea glutinosae Br.-Bl. et R.Tx. 1943) are present in the rivers floodplains and other lower terrain of all loess “islands”, but most of all - on the territory of the Berezna-Mena-Sosnytsia and Ripky-Chernihiv loess ”islands”. The broad-leaved forests are preserved only in small massifs. They are mainly represented by plant communities belonging to the Carpino-Fagetea sylvaticae Jakucs ex Passarge 1968 and Quercetea robori-petraeae Br.-Bl. ex R.Tx. 1943 classes. The forest-steppe pine forests of the Pyrolo-Pinetea sylvestris Korneck 1974 class rarely occur on loess “islands”. These phytocenoses occupy forest strips and artificial pine plantations on the site of felled broad-leaved forests. In general, the lowest number of the forest vegetation associations is recorded on the territory of the Mykhailo-Kotsyubinsky loess “island”. The Sedniv-Tupychiv and Berezna-Mena-Sosnytsia loess “islands” have a similar syntaxonomic richness (the associations number).